Molecular basis for resistance to fluazifop-p-butyl in itchgrass (rottboellia cochinchinensis) from Costa Rica - Castillo Matamoros, Rolbin Esteban (2016)
Rottboellia cochinchinensis is an annual grass weed species known as itchgrass, or “caminadora” in America´s Spanish speaking countries, and has become a major and troublesome weed in several crops. The application of fluazifop-P-butyl at recommended rates (125 g a.i. ha-1) was observed to be failing to control itchgrass in a field in San José, Upala county, Alajuela province, Costa Rica. Plants from the putative resistant R. cochinchinensis population survived fluazifop-P-butyl when treated with 250 g a.i. ha-1 (2X label rate) at the three- to four-leaf stage under greenhouse conditions. PCR amplification and sequencing of partial carboxyl transferase domain (CT) of the acetyl-CoA carboxylase (ACCase) gene were used to determine the molecular mechanism of resistance. A single non-synonymous point mutation from TGG (susceptible plants) to TGC (putative resistant plants) that leads to a Trp-2027-Cys substitution was found. This Trp-2027-Cys mutation is known to confer resistance to all aryloxyphenoxyproprionate (APP) herbicides to which fluazifop-P-butyl belongs. To the best of our knowledge, this is the first report of fluazifop-P-butyl resistance and a mutation at position 2027 for a Costa Rican R. cochinchinensis population.